Comparison of conventional adult-single-lid-retraction-by-thumb-method with two-thumb and two-bud methods in eye drop instillation prior to retinopathy of prematurity screening in neonates and infants - Bali Jatinder (Journal of Clinical Ophthalmology and Research, 2013)
In our retinopathy of prematurity (ROP) screening program we found that babies tended to show poor, erratic and variable response to mydriatic drug instilled prior to ROP screening. We compared the adult Single-lid Retraction by Thumb Method (SRTM) with two-thumb-retraction-method (TTM) and the two-bud-instillation-method (TBM). Thirty instillations each for the three methods were studied using computerized randomization. Neonates with plus disease, Iris neovascularization and threshold ROP were excluded from study. Instillations were carried out by nurses and residents, who rated the ease of administration on a 5 point Likert Scale administered as a visual analog scale (5 = fully satisfied and 1 = fully dissatisfied). The instillation was rated as successful if the drop was instilled in the cul de sac and unsuccessful if delivered outside it in the first attempt. Second attempts and change of technique were considered unsuccessful. The percentage of successful instillations in the first attempt was 36.7% in SRTM, 70.0% in TTM and 83.3% in TBM (χ2 = 14.928, P = 0.001; Chi-square test). The mean ranks for the ease of administration were 43.02, 57.00, and 36.48 for the SRTM, TTM, and TBM methods respectively (H(2) =10.367, P = 0.006; Kruskal-Wallis test). SRTM failed in most cases on first attempt (67.3%). TBM was significantly more difficult than TTM or the SRTM. SRTM should not be recommended for infants and neonates in pediatric ophthalmology practices and ROP screenings in nurseries. However, larger studies are required to validate the findings of present study.